CAN YALE ENDOWMENT MODEL BE APPLIED FOR ISLAMIC PENSION FUND? - Tumewang, Yunice Karina (Journal of Islamic Monetary Economics and Finance, 2018)
This paper examines Yale Endowment model and proposes a modified investment model to achieve an investment objective of mainstream investors and to comply with Sharia principle. The proposed model utilizes Islamic CAPM to formulate the optimal asset allocation for Islamic pension fund’s portfolio. It will offer a strong investment strong which could be adopted by government to manage the Islamic pension fund and raise the awareness of society to see the great potential of Islamic pension fund in the future. Promoting an efficient and productive investment of pension-fund assets not only helps reaching Sustainable Development Goals (SDGs) by providing important sources of long-term finance for development, supporting financial inclusion and ensuring that poverty among the elderly is alleviated by a strong growth and resilience of income in retirement through pension systems that have broad coverage.